Squamous cell carcinoma at the site of ileo-anal pouch in Crohn’s disease - Condurache, Dorina Gabriela (BMJ Case Rep, 2021)
Few cases of pouch-related cancers have been reported in inflammatory bowel disease, and squamous cell carcinoma (SCC) is very rare. We have reviewed the published literature searching the online databases PubMed and Medline. Since 1979, there have been eight cases of SCC developing after restorative proctocolectomy in ulcerative colitis. To date, there have been no reported cases of SCC of the ileo-anal pouch in Crohn’s disease. We present the case of a 59-year-old woman who underwent colectomy with ileal pouch-anal anastomosis for Crohn’s disease during the 1990s. The patient was noted to be anaemic and was experiencing significant weight loss with poor pouch function in 2019. Endoscopy with histology and radiological investigation revealed the presence of SCC of the pouch. This was subsequently treated with surgical therapy and chemoradiotherapy.